2020
DOI: 10.1590/0004-282x20200032
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in patients with narcolepsy types 1 and 2 from a Sleep Center in Brazil

Abstract: ABSTRACT Introduction: Narcolepsy patients have higher prevalence of comorbidities, such as obesity, depression, and pain. Narcolepsy symptoms and concomitant medical conditions can impact the daily activities of patients. The objective of this study is to describe the quality of life in a sample of patients with narcolepsy, and the influence of the nutritional status in health domains. Methods: At Unifesp, two groups of 33 patients (narcolepsy types 1 and 2 meeting 2014 criteria, concerning hypocr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“… 45 Managing these comorbidities is crucial to enhancing the well-being of these patients, directly impacting their overall quality of life. 11 …”
Section: Comorbiditiesmentioning
confidence: 99%
See 2 more Smart Citations
“… 45 Managing these comorbidities is crucial to enhancing the well-being of these patients, directly impacting their overall quality of life. 11 …”
Section: Comorbiditiesmentioning
confidence: 99%
“…Poor health status has been noted in Brazilians with narcolepsy type 2, suggesting that obesity negatively impacts physical domains. 47 …”
Section: Comorbiditiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies of the quality of life of NT1 and NT2 revealed incongruent results. A recent study reported that the physical role functioning score of SF-36 was lower in NT1 than in NT2 and controls ( 7 ), while another study showed no difference in the total score between NT1 and NT2 ( 8 ).…”
Section: Introductionmentioning
confidence: 97%
“…Patients with NT1 have cataplexy (sudden muscles weakness often triggered by strong emotions) and/or a low or unmeasurable hypocretin-1 level in cerebrospinal fluid (CSF), whereas those with NT2 do not have cataplexy and their CSF hypocretin level is > 110 pg/ mL or unmeasurable. Studies have revealed that those with narcolepsy not only have sleep or wake-related problems, such as hypersomnia and excessive daytime sleepiness, but also have poorer quality of life [15][16][17][18][19][20][21][22] and more physical and psychiatric comorbidities (e.g., obesity, sleep apnea, depression, and anxiety), than general population [23][24][25]. Other narcoleptic symptoms can result in considerable distress and increased vulnerability, including cataplexy, hypnogogic or hypnopompic hallucination (hallucinatory experience when falling asleep or waking up), sleep paralysis (the inability to move or speak when falling asleep or waking up), and disturbed nighttime sleep [26].…”
Section: Introductionmentioning
confidence: 99%